Continuous cell separation using dielectrophoresis through asymmetric and periodic microelectrode array - Chian, Kerm Sin (MAE) (2013)
The study presents a dielectrophoretic cell separation method via three-dimensional (3D) nonuniform electric fields generated by employing a periodic array of discrete but locally asymmetric triangular bottom microelectrodes and a continuous top electrode. Traversing through the microelectrodes, heterogeneous cells are electrically polarized to experience different strengths of positive dielectrophoretic forces, in response to the 3D nonuniform electric fields. The cells that experience stronger positive dielectrophoresis are streamed further in the perpendicular direction to the fluid flow, leaving the cells that experience weak positive dielectrophoresis, which continue to traverse the microelectrode array essentially along the laminar flow streamlines. The proposed method has achieved 87.3% pure live cells harvesting efficiency from a live/dead NIH-3T3 cells mixture, and separation of MG-63 cells from erythrocytes with a separation efficiency of 82.8%. The demonstrated cell separation shows promising applications of the DEP separator for cell separation in a continuous mode.